First Five Year Plan Bombay State Surat District - Government of Bombay (My University, 1954)
The First Five-Year Plan for Surat District (1951-52 to 1955-56) presents a detailed framework for socio-economic development, integrating agriculture, irrigation, education, public health, infrastructure, and community welfare initiatives in alignment with national and state objectives. Irrigation projects, notably the Kakrapar Weir and Canal, aimed to enhance irrigation over 652,000 acres, improving rice and cotton yields while mitigating floods. Agricultural development included khar land reclamation, soil improvement, and mechanization, alongside the promotion of cooperative societies and cottage industries supporting 23% of local employment. Educational reforms encompassed free and compulsory primary education, expansion of schools from 852 to 1,418, teacher training, vocational education, and literacy programs, while health measures included the establishment of hospitals, dispensaries, safe water supply schemes, sanitation projects, and an extensive anti-malaria campaign. Infrastructure investments focused on road construction, port modernization, and power distribution through the South Gujarat Electric Grid. Special emphasis was placed on backward classes, with educational scholarships, economic incentives, and reserved government job opportunities, complemented by labor welfare initiatives through adult education and recreational programs. Local development works, funded jointly by central and state governments, prioritized water supply, rural sanitation, and community participation, emphasizing sustainable and inclusive growth. Overall, the plan reflects a multi-sectoral strategy to uplift living standards, foster equitable development, and integrate diverse communities into the broader socio-economic framework of Surat District.
Surat District
Surat District
Keywords: Surat District; State Five Year Plan; Irrigation Projects; Agricultural Development; Education Initiatives; Public Health; Road Infrastructure; Cottage Industries; Cooperative Societies; Power Projects; Backward Classes; Local Development